Kemitraan berbasis masjid: pemutaran compact disc â€œsehat jiwa ragaâ€ untuk sosialisasi perilaku hidup bersih dan sehat - Hartiningsih, Dini; Agustin, Helfi (Jurnal Cakrawala Promkes, 2021)
The Yogyakarta City Government launched an innovation in health promotion at mosques, named the "healthy outside and inside" in 2015. This program is a partnership with the mosque keeper to promote clean and healthy living habits. No studies have yet evaluated the extent of the success of the program. This study aims to see the effectiveness of the program in changing people's healthy behaviour. This type of research is an analytic survey with a cross-sectional study approach. The research location is in the working area of the Umbulharjo Community Health Center. The population is 4608 families. The number of samples is 108 people who live around the mosque. The inclusion criteria is the housewives because they have a lot of time at home, so there are more opportunities to be exposed to Compact Disc (CD) in mosques than other people who work outside the home. The exclusion criteria were people who were unwilling and deaf. The sampling technique is a probability proportionate to size, namely by taking the sample referring to mosques that play CDs and those that do not play with 2 : 1 ratio. The control variables are age and level of education. Data were collected through a questionnaire and analyzed by Mann Whitney-test. The results showed a difference in the community's mean knowledge and attitudes around the mosque playing (69.44) and not playing the health promotion CD (60.14). The Mann Whitney-test results obtained a p-value of 0.00, which means there is an effect of CD health promotion playing on the level of public knowledge about PHBS. The playing CD health promotion at mosques in Umbulharjo District, Yogyakarta, has benefited from increasing housewives' knowledge about healthy and clean behaviour.